1996
DOI: 10.1177/01461672962212009
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination in the Minimal Group Paradigm: Social Identity or Self-Interest?

Abstract: Social identity theory (SIT) proposes that discrimination reflects competition for a positive social identity. In contrast, the behavioral interaction model (BIM) proposes that self-interest and interdependence of fate are at the root of discrimination. Using the minimal group paradigm, 94 undergraduates were randomly categorized as group members in a 2 (Interdependence: autonomous/interdependent) × 2 (In-group Identification: low/high) factorial design. Before distributing resources, autonomous participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
1
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 26 publications
5
104
1
2
Order By: Relevance
“…We suggest the following interpretation of anticipated samegroup favoritism with respect to group identity and ingroup favoritism. Previous research on social identity has shown that the attitudes and behavior of strongly identified people toward ingroup members is more favorable than toward outgroup members (Gagnon & Bourhis, 1996;Hewstone et al, 2002). Thus, people repeatedly interact in daily life with strongly identified others who favor samegroup members.…”
Section: Discussionmentioning
confidence: 98%
“…We suggest the following interpretation of anticipated samegroup favoritism with respect to group identity and ingroup favoritism. Previous research on social identity has shown that the attitudes and behavior of strongly identified people toward ingroup members is more favorable than toward outgroup members (Gagnon & Bourhis, 1996;Hewstone et al, 2002). Thus, people repeatedly interact in daily life with strongly identified others who favor samegroup members.…”
Section: Discussionmentioning
confidence: 98%
“…Considerable work has replicated and honed the early research, demonstrating that mere categorization results in bias favoring the in-group, including enhanced evaluations, more internal attributions for positive behaviors, more external attributions for negative behaviors, and positive discrimination in the distribution of rewards (Brewer & Brown, 1998;Deaux, Reid, Mizrahi & Cotting, 1999;Gagnon & Bourhis, 1996). Scholars have concluded from this substantial body of literature that in-group bias and out-group discrimination are a fundamental dynamic present in all human groups that organizations should be aware of and try to mitigate.…”
Section: Minimal Intergroup or Macro-historical Paradigm?mentioning
confidence: 96%
“…Gagnon & Bourhis, 1996;Hodson, Dovidio, & Esses, 2003;Liebkind et al, 2004) the notion that identification is associated with discrimination. According to SIT, this connection could be expected only when particular conditions are met, for instance, when intergroup comparison is stressed and the context provides relevant evaluative dimensions for intergroup comparison (McGarty, 2001;Voci, 2006).…”
Section: Covariatesmentioning
confidence: 99%